Effect of chronic ethanol feeding on rat hepatocytic glutathione. Compartmentation, efflux, and response to incubation with ethanol. - Fernandez-Checa, J C (1987)
Hepatocytes from rats that were fed ethanol chronically for 6-8 wk were found to have a modest decrease in cytosolic GSH (24%) and a marked decrease in mitochondrial GSH (65%) as compared with pair-fed controls. Incubation of hepatocytes from ethanol-fed rats for 4 h in modified Fisher's medium revealed a greater absolute and fractional GSH efflux rate than controls with maintenance of constant cellular GSH, indicating increased net GSH synthesis. Inhibition of gamma-glutamyltransferase had no effect on these results, which indicates that no degradation of GSH had occurred during these studies. Enhanced fractional efflux was also noted in the perfused livers from ethanol-fed rats. Incubation of hepatocytes in medium containing up to 50 mM ethanol had no effect on cellular GSH, accumulation of GSH in the medium, or cell viability. Thus, chronic ethanol feeding causes a modest fall in cytosolic and a marked fall in mitochondrial GSH. Fractional GSH efflux and therefore synthesis are increased under basal conditions by chronic ethanol feeding, whereas the cellular concentration of GSH drops to a lower steady state level. Incubation of hepatocytes with ethanol indicates that it has no direct, acute effect on hepatic GSH homeostasis.